Graded synthesis of highly ordered MCM-41 and carbon/zeolite composite from coal gasification fine residue for crystal violet removal. (20th December 2020) - Wu, Yu-Hua; Ma, Yu-Long; Sun, Yong-gang; Xue, Kai; Ma, Qiao-Ling; Ma, Ting; Ji, Wen-Xin
Abstract: The utilization of coal gasification slag currently has become a central issue in both coal and environmental science. Coal gasification slag has been used as raw materials to synthesize the porous materials. However, for the synthesis of these materials, the high temperature was needed, and not all coal gasification slag could be converted to. This work developed a new strategy to graded synthesis of MCM-41 and carbon/zeolite composite from coal gasification fine residue (CGFR) under mild conditions. By this way, graded preparations of valuable porous materials from CGFR could realize the efficient conversion and utilization of CGFR. The synthesized MCM-41 exhibited highly ordering feature with hexagonal arrays and the straight 1D channels. The MCM-41 zeolite had large surface areas and narrow pore diameter distribution. The different synthesis conditions of MCM-41 from CGFR, such as acidification process, gel pH, crystallization temperature and crystallization time were discussed. As to the synthesized carbon/zeolite composite, it presented a P-type zeolite with the flower-like shape on the substrate of carbon with low degree graphitization. The carbon/zeolite composite had the total specific surface area of 189.27 m 2 g −1 and exhibited thermal stability below 300 °C. Meanwhile, the synthesis of carbon/zeolite composite with different alkali dissolution time was also investigated. Besides, the adsorption experiments of toxic crystal violet in water indicated that these two porous materials had potential applications in adsorption and removal of harmful pollutants. Highlights: MCM-41 and carbon/zeolite composite were staged synthesized from CGFR. MCM-41 with large BET of 1013 m 2 g −1 exhibited five characteristics diffraction peaks. The carbon/zeolite composite with BET of 189.27 m 2 g −1 had good thermal stability. MCM-41 and carbon/zeolite composite had good performance for crystal violet remove.